The Effect of Budget Participation on Local Government Performance with Organizational Commitment as Moderating Variable - Arvindy Rivito; Sri Mulyani (Journal of Accounting Auditing and Business, 2019)
Since 2003, a performance-based budgeting process has been implemented in local governments in Indonesia. This budgeting process requires participation from organizational members in submitting budget proposals. Commitments from members of the organization are also needed. With this performance-based budgeting, governance is expected to be efficient and effective. The performance of local governments in Indonesia has also increased in recent years. This study aims to analyze the effect of budget participation and organizational commitment on the performance of local governments. The research was conducted in the City Government of Bandung. The method used in this research is descriptive analytical method. In this study, organizational commitment became moderating variable, so that data analysis used moderating regression analysis. The sample in this research is all work units (Satuan Kerja Perangkat Daerah) in the Bandung City Government.  The results showed that budgetary participation had a positive effect on the performance of local governments. While organizational commitment strengthens the positive influence of budget participation on the performance of local governments.